Peppermint soda - Simon, Yves 1944- (BFI, 2017)
"Teenage sisters Anne and Frédérique couldn't be more different: introverted Anne is trying to understand the world around her as she's on the threshold of adolescence; while outgoing, politically aware Frédérique is beginning her first love affair. This coming-of-age tale, the debut feature of underrated French director Diane Kurys ("Entre nous", "Sagan"), is an ode to teenage summers, first kisses and first losses. Offering an intricate view of adolescence in 1960s France, Peppermint Soda recalls Francois Truffaut's Les quatre cents coups and encapsulates the upsurge in liberality during this radical period." [amazon.co.uk]
Original: Frankreich 1977
Bildformat 1.66:1
Special features: presented in high definition and standard definition ; original theatrical trailer ; interview with Diane Kurys (2008, 33 mins): an interview with the director ; scrapbook (2008, 3 mins): Diane Kurys explores her collection of photographs and production materials ; illustrated booklet with full film credits and new essays by Sophie Mayer and Michael Brooke